Padronização e validação de um novo modelo de febre induzida pela injeção intratecal de prostaglandina E2 em ratos jovens - Ratzlaff, Viviane (2006)
The fever response, besides being part of host defense response to infection or inflammation, is associated with discomfort and anxiety and may constitute a risk for febrile seizures in children. Therefore, antipyretic therapy is routinely prescribed for febrile patients. The animal models of fever using the systemic injection of lipopolysaccharide (LPS) and Baker yeast, described in the literature, are suitable for screening of novel antipyretics, but they do not provide information regarding the mechanism of action of these compounds. Therefore, the present study aimed to describe and validate a model of fever induction by prostaglandin (PG) E2, the final mediator of febrile response in the central nervous system, in young male Wistar rats (25-30 days of age). In this protocol, PGE2 was injected intrathecally without implantation of cannula. Rectal temperature (TR) was recorded every thirty minutes for three hours after PGE2 injection (08:00 11:00 h). The intrathecal (i.t.) injection of PGE2 10 ηg in 100 μL/animal induced fever in the animals, which was prevented by administration of EP1 and EP3 receptors antagonists, but did not by antagonist of EP4 receptor. In addition, the classic antipyretics dipyrone and acetaminophen, at doses that had no effect per se on TR of animals, did not revert the fever induced by i.t. injection of PGE2. This model seems suitable to investigate whether the action of antipyretics occurs upstream or downstream the prostaglandin coupling in EP receptors. In addition, this protocol is advantageous from the technical, ethical and economical point of view compared to others PGE2-induced fever protocols described in the literature, because trepanation for cannula implantation is not required, reducing the inflammatory response, animals suffering and experimental costs.